Internal Control Practices and Performance of Saving and Credit Scheme Organizations in Uganda: A Case Of Rukiga Sacco Ltd. - Kiconco, Patience (Kabale University, 2023)
This study was carried out in Rukiga District to investigate how internal control affects Rukiga SACCO's performance. The study's predictor variables included separation of duties, independent review, and risk management, and Rukiga SACCO's performance included growing its loan portfolio, improving its profitability, and expanding its market share. The study was based on three objectives namely: to assess the effect of Segregation of duty on the performance of Rukiga SACCO; to determine the effect of Independent check on the performance of Rukiga SACCO; and, to determine the effect risk management on financial performance of Rukiga SACCO. The cross-sectional survey was followed by the study. Data from 135 respondents was gathered, quantitative analysis was performed, and qualitative analysis was also performed. Frequency tables were employed to describe the data since descriptive analysis required presentation of a single variable and its characteristics. A Pearson correlation matrix was used to determine the correlations between the predictor factors and the dependent variable at the bivariate level. To fit the data, a linear regression model was employed. Segregation of duties (R=762), independent checks (R=676), and risk management (R=899) have a positive importance on the performance of Rukiga SACCO in Rukiga District, according to research findings from the regression model. The key finding of this study is that risk management, segregation of duties, and independent checks all significantly affect Rukiga SACCO performance. Therefore, the study recommends that additional work should be put into task segregation, independent auditing, and risk management to realize loan portfolio expansion, profitability growth, and market share growth as essential components of Rukiga SACCO's performance in Rukiga District.